Modelling, implementation and performance analysis of a hybrid wind solar power generator with battery storage - Karimi, Zeinab Mousavi (2014)
Dissertação de Mestrado em Energia para a Sustentabilidade apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra